2022
DOI: 10.1080/08995605.2022.2041995
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal studies on cohesion in a military context – A systematic review

Abstract: Cohesion is one of the most studied group phenomena and there is an agreement among scholars today that cohesion is a key contributor to team functioning and performance. A large body of research has shown that cohesion has several positive effects on psychological, social, and behavioral outcomes. Since research on cohesion has increased significantly in recent decades there is a need for an updated overview of research regarding antecedents and outcomes of cohesion in a military context. In this paper, a sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…According to Goodwin et al (2018) team effectiveness has been a significant focus of military research for decades in order to guarantee that military teams have the human skills necessary to effectively fulfil their tasks and handle future problems. This further confirms by the findings of Fors -Brandebo et al (2022). According to Fors -Brandebo et al…”
Section: вісник кафедри юнеско «неперервна професійна освіта ххі стол...supporting
confidence: 89%
“…According to Goodwin et al (2018) team effectiveness has been a significant focus of military research for decades in order to guarantee that military teams have the human skills necessary to effectively fulfil their tasks and handle future problems. This further confirms by the findings of Fors -Brandebo et al (2022). According to Fors -Brandebo et al…”
Section: вісник кафедри юнеско «неперервна професійна освіта ххі стол...supporting
confidence: 89%
“…Longitudinal studies hold the potential to bridge the current gaps in understanding the complex relationship between vitamin D levels and rheumatoid arthritis, paving the way for more tailored and effective treatment approaches in the future. (Maria Fors Brandebo et al, 2022) [30] .…”
Section: Future Directions and Recommendations Need For Longitudinal ...mentioning
confidence: 98%
“…While work engagement (Bakker et al, 2008) resembles the construct of work effectiveness, work engagement is comprised of psychological factors that predict work effectiveness (Macey & Schneider, 2008). A review of studies conducted in the military context have found that cohesion and leadership predict work performance (Fors Brandebo et al, 2022). In addition, meta-analyses of research on perceived organizational support have found associations with task performance (Riggle et al, 2009) and in-role performance (Kurtessis et al, 2017).…”
Section: Work Effectivenessmentioning
confidence: 99%